Strategies for Enhancing Zakat Fund Management in Minority Areas: a Case Study in Humbang Hasundutan Regency - Jhon Anwar Tumanggor; Yayat Sujatna (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2023)
This study focuses on analyzing two key aspects: zakat collection strategies and the effectiveness of zakat management in Islamic minority regions, particularly in Humbang Hasundutan Regency. Employing a descriptive method with a quantitative approach, the analysis of zakat collection strategies utilizes the SWOT technique, while the effectiveness of zakat management is assessed through the ZCP 10-point instrument, specifically targeting Disbursement Management. The findings indicate that the Zakat Collection Unit (UPZ) of BAZNAS in Humbang Hasundutan falls within the